A survey on the choice of UPV-CM students for the 2004 Philippine President - Borongan, Helen Rose; Cuevas, Pamela T.; Heria, April Katrina T.; Necor, Marievic F.; Pagulong, Gladys Gay B.; Villanueva, Jenny Rose R.
This study primarily aimed to determine the choice of UPV-CM students for the 2004 Philippine President and the criteria with which they will be using in making their choice. Out of the 936 total population of students enrolled at the College of management, the researchers selected 90 students as respondents, grouped according to gender, year level, degree program, and income. The sample size was derived using the Slovin's formula. This descriptive-quantitative research utilized a questionnaire as survey instrument for dfata gathering. the researchers made use of the SPSS to analyze the data gathered. Results show that the primary criteria that CM students highly consider in choosing the next Philippine POresident is educational attainment. Television appeared as the most frequent source of information about candidates. Eighty-one percent of the respondents said that their decision in choosing a candidate is affected by issues and controversies, while 19% of the population is influenced by surveys. Honesty as a personal quality is being preferred in the candidate, with 82% of the respondents sayong so. Determination and open-mindedness are also looked for. It was also found out that majority of the respondents, which was approximately 38%, had difficulty in choosing their candidates for President. Seventy-seven percent of the respondents were decided in their choice for President, and with that, 48% had said that they are already firm with their decision, and the rest are still open to suggestions or changes. Raul Roco came oput as the choice for President of the UPV-CM students.